Detailed knowledge of maternal and infant factors and human milk composition could inform recommendations for optimal composition. (17th November 2021) - Demmelmair, Hans; Koletzko, Berthold
Abstract: Breastfeeding is best for infants, but quantitative associations between specific milk components and infant biomarkers remain unclear. Methodological limitations include missing milk volume intake, variable milk composition and that standardised, fasted state blood sampling is impossible in infants. Milk protein and fat content appear marginally related to infant serum amino acid and phospholipid concentrations, with some association between milk fatty acid composition and lipid species levels. Conclusion: Detailed simultaneous examinations of maternal factors, milk composition and infant biomarkers or outcomes could identify the mechanistic basis of human milk effects and help develop dietary recommendations for optimal human milk composition.